Agama dan Pendidikan di Barat dan Dunia Islam - Akhmad Syahbudin; Zulfa Jamalie; Irfan Noor; Muhammad Iqbal; Abd. Basir (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
There has been a struggle in the diversity of the Western world, such as: That religion whose adherents have absolute, universal, and transcendental truths was concretely visualized in the Western World in the Middle Ages, even the West in the Middle Ages was known as the century of faith. However, in the modern era, the West, starting with the birth of a religious Renaissance, was challenged, criticized, and at least suspected. Since the renaissance there have been efforts to bring the Western world towards scularism and the separation of the role of religion in the life of empirical reality. The peak of rejection of religion in the west was raised by Nietzie with the statement God Is Death. In the postmodern century, it is nothing more than an image that has no meaning. Even religion has always been used as material for discussion, but in empirical reality and in practical life the existence of religion is considered as something that has no relation and is considered to interfere with human freedom. Postmodernism has a philosophy of anti-absoluteness and certainty, including in relation to religion. Therefore in the Western world there is no certainty in religion.